Including smallholders with vertical coordination - Linda Bitsch; Silva Atoyan; Barbara Richter; Jon Hanf; Taras Gagalyuk (Agricultural Economics, 2021)
The current chapter demonstrates an application of the theoretical framework of vertical coordination, more specifically the application of contracting in productive partnerships, to integrate smallholders into the value chain of a specialised crop. The aim of the chapter is to derive implications for industry participants on how to integrate smallholders with vertical coordination. Therefore, we take a closer look on vertical coordination and contracting in productive partnerships. We have taken the value chain of brandy production in Armenia and used the Yerevan Brandy Company (YBC) to perform our case study, with which we can analyse vertical coordination mechanisms used by the company. Further, we want to identify factors that drive processors and smallholders to enter into contracts. Qualitative interviews were conducted with the YBC, their grape suppliers, as well as experts from related fields. We analysed the data with a qualitative content approach. Results show that the YBC uses different measures of vertical coordination, i.e., contracts and farm assistance in the form of consultancy and input supply. The company tends to use production contracts rather than pure marketing contracts, as it is actively engaged in the production process. The use of contract farming is beneficial for both the processing company and the smallholders.
Keywords: 630; value chain; vertical coordination; contracting; smallholders; brandy; Armenia